Friend Recommendation System by Using Context-Awareness - Akanksha Pal, Abhishek Singh Rathore (International Journal of Advanced Science and Technology, 2020)
Abstract: In current scenario, everybody is busy but still wants to be socially active to share their knowledge. Recommendation of friends with similar interest is the biggest challenge for the social networking applications. This can be accomplished by user’s lifestyle that plays the major role in identifying user nature and interest.  Lifestyle with contextual information based friend recommendation system is different and more precise approach. Moreover, users’ interests are not static, it may be varied with time. Keywords: Recommendation System, Machine Learning, User Interest, Friend Recommendation.